Photodynamic Surgery for Feline Injection-Site Sarcoma. (8th July 2019) - Martano, Marina; Morello, Emanuela; Avnet, Sofia; Costa, Francesco; Sammartano, Federica; Kusuzaki, Katsuyuki; Baldini, Nicola
Abstract : Musculoskeletal sarcomas are rare and aggressive human malignancies affecting bones and soft tissues with severe consequences, in terms of both morbidity and mortality. An innovative technique that combines photodynamic surgery (PDS) and therapy (PDT) with acridine orange has been recently suggested, showing promising results. However, due to the low incidence of sarcoma in humans, this procedure has been attempted only in pilot studies and stronger evidence is needed. Naturally occurring tumors in cats are well-established and advantageous models for human cancers. Feline injection-site sarcoma (FISS) shares with human musculoskeletal sarcomas a mesenchymal origin and an aggressive behavior with a high relapse rate. Furthermore, wide surgical excision is not always possible due to the size and site of development. We assessed the feasibility and the effectiveness of PDS and PDT with acridine orange to prevent FISS recurrence by treating a short case series of cats. For PDS, the surgical field was irrigated with an acridine orange solution and exposed to UV light to enlighten the residual tumor tissue, and the resultant fluorescent areas were trimmed. For PDT, before wound closure, the field was again irrigated with acridine orange solution and exposed to visible light to get the antitumoral cytocidal effect. The procedure was easy to perform and well tolerated, we did not observe any major complications, and all the surgical resection margins were free of disease. Finally, at follow-up, all treated patients did not show evidence of tumor recurrence and had a significantly higher event-free survival rate in respect to a control group treated only by surgery. In conclusion, by this study we demonstrated that, in FISS, PDS and PDT with acridine orange may improve local tumor control, granting a better outcome, and we laid the foundation to validate its effectiveness for the treatment of human musculoskeletal sarcomas.